The status of conservation and management of indigenous sheep breeds in South Africa - A review - Motaung, Thabang Godfrey; Osotsi, Joab Malanda; Mujitaba, Malam Abulbashar; Wanjala, George; Novotni-Dankó, Gabriella (Acta Agraria Debreceniensis, 2024)
Indigenous sheep breeds in South Africa play an important role in local food security and they are adapted to local conditions. Their genetic and cultural values have to be recognised for national importance. The conservation of these breeds is very critical as most of them are already classified as endangered. The South African government has the initiative to attempt the conservation of these animals; however, it comes with several challenges. In addition to funding, breed conservation demands farmers to understand and recognise the role of such breeds in society. This is especially crucial in the rural communal lands where breeds are kept. Farmers that raise indigenous breeds should be taught the necessity of maintaining the purity of these breeds. Indigenous sheep breeds in South Africa are not favored by the commercial farmers and thus they are more vulnerable. This review outlines the nature of sheep farming and the conservation status of four indigenous sheep breeds in South Africa. The effort and challenges that are met in current conservation arrangements are discussed. Moreover, we emphasise on the conservation techniques that are employed in South Africa.